СОЗДАНИЕ ИНФОРМАЦИОННОЙ СИСТЕМЫ ОБЕСПЕЧЕНИЯ РАБОТ ПО ГЕОЛОГИЧЕСКОМУ ИЗУЧЕНИЮ НЕДР И ВОСПРОИЗВОДСТВУ МИНЕРАЛЬНО-СЫРЬЕВОЙ БАЗЫ - Чесалов Л.Е.; Суханов М.Г. (My University, 2006)
The system are developed for Rosnedra Federal Agency. Goals of the system are defined. System architecture is described, and various subsystems are detailed into. Suitable communication and software decisions are proposed.
Keywords: 55:681.3